Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1093/bja/aei198
|View full text |Cite
|
Sign up to set email alerts
|

Allergic reactions in anaesthesia: are suspected causes confirmed on subsequent testing?

Abstract: An informed guess is not a reliable way of determining the cause of a supposed allergic reaction during anaesthesia and may put a significant number of patients at unnecessary risk. Some patients may be labelled with a wrong allergy, leading to unnecessary warnings against harmless substances, and some patients may be put at risk of subsequent re-exposure to the real allergen. Patients with suspected allergic reactions during anaesthesia should be referred for investigation in specialist centres whenever possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 10 publications
2
48
0
4
Order By: Relevance
“…This reinforces the message conveyed by Kroigaard and colleagues in 2005 [5], who said that an informed guess is not a reliable way of determining the cause of a suspected hypersensitivity reaction, a fact compounded by the high number of different drugs administered in a short period of time during anaesthesia. It is also worrying that 10% of anaesthesia-related immediate hypersensitivity reactions reported to the UK Medicines Control Agency were fatal [43].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This reinforces the message conveyed by Kroigaard and colleagues in 2005 [5], who said that an informed guess is not a reliable way of determining the cause of a suspected hypersensitivity reaction, a fact compounded by the high number of different drugs administered in a short period of time during anaesthesia. It is also worrying that 10% of anaesthesia-related immediate hypersensitivity reactions reported to the UK Medicines Control Agency were fatal [43].…”
Section: Discussionsupporting
confidence: 79%
“…A study from 2005 showed that an informed guess was not a reliable way of determining the cause of a suspected hypersensitivity reaction during anaesthesia, and may put a significant number of patients at unnecessary risk [5]. The aims of our service were: to determine the cause of the event; to identify any agent responsible; to determine those drugs which were safe to use in future anaesthetics; and to make recommendations for safe peri-operative care.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective survey comparing suspected causes with the result of subsequent testing found that, in 49 of 67 cases, the suspected agent did not match testing results. 9 Tryptase, a protease released from activated mast cells, can be used as a marker of immune activation. An elevated serum tryptase concentration in blood drawn within several hours after the event can be helpful, although it cannot differentiate between anaphylaxis and an anaphylactoid reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Severe, potentially life-threatening anaphylaxis from simple cutaneous application such as perioperative skin disinfection and wound cleansing remains anecdotal and probably underestimated. In a recent survey, chlorhexidine accounted for 27% of the overlooked perioperative hypersensitivity reactions (171). Note that this prevalence of chlorhexidine anaphylaxis is not observed in other countries.…”
Section: Chlorhexidine and Other Antisepticsmentioning
confidence: 94%